The Impact of Modifying Lema (Lego and Maze) Game on Stimming Behaviors in Children with Autism Spectrum Disorder (ASD) - Marta Pastari; Meilina Meilina; Sri Martini; Sri Endriyani; Heni Sumastri (GLOBAL HEALTH SCIENCE GROUP, 2024)
ABSTRACT Children with Autism Spectrum Disorder (ASD) often exhibit self-stimulation behaviors (stimming), such as repetitive movements, sounds, or actions, which can disrupt therapy sessions and social interactions. These behaviors can impede the development of social skills and focus. Given the importance of non-invasive interventions, modifying play-based activities such as LEGO and maze games (LEMA) has been explored as a potential method to reduce stimming behaviors. (LEMA) game on reducing self-stimulation (stimming) behaviors in children with Autism Spectrum Disorder (ASD). The research employed an A-B-A design, including a baseline phase (A1), an intervention phase (B), and a post-intervention phase (A2), conducted over 12 sessions. Two children, RFQ and HG, both of whom exhibited frequent stimming behaviors, were selected as participants. The intensity of their stimming behaviors was measured before and after the intervention using observational data. The data were analyzed using visual analysis to identify changes in the frequency and intensity of stimming behaviors across phases. Additionally, percentage of non-overlapping data (PND) was calculated to evaluate the effectiveness of the intervention data. The findings showed that stimming behaviors in both children, which originally lasted approximately 390 seconds during the baseline phase (A1), significantly decreased during the intervention phase (B), with durations reduced to 48-55 seconds. After the intervention was stopped, stimming behaviors remained reduced in the post-intervention baseline phase (A2), indicating the effectiveness of the LEMA game in reducing these behaviors. Modifying the LEGO and Maze (LEMA) game effectively reduced self-stimulation behaviors in children with ASD. The results align with previous studies suggesting that structured play interventions, like LEGO and maze activities, can enhance focus and reduce repetitive behaviors in children with ASD.